1987
DOI: 10.2118/12744-pa
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Seismic Methods for Remote Monitoring of Thermal EOR

Abstract: Summary Laboratory measurements of compressional (P) and shear (S) wave velocities and first-arrival amplitudes at ultrasonic frequencies (0.65 to 1.70 MHz [0.65 × 106 to 1.70X 106 cycles/sec]) in unconsolidated tar and heavy-oil sands indicate that wave-propagation properties in these materials are sensitive to bitumen content. Studies made at elevated temperatures, overburden pressures, and pore pressures revealed that heat and oil content in Venezuelan, Californian, and Canadian reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The theoretical model based on the wave propagation equations of de la Cruz and Spanos also predicts an intrinsic attenuation dependence on temperature. The predicted effect on attenuation with increasing temperature was found to be in qualitative agreement with measurements by Tosaya et al (1987).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The theoretical model based on the wave propagation equations of de la Cruz and Spanos also predicts an intrinsic attenuation dependence on temperature. The predicted effect on attenuation with increasing temperature was found to be in qualitative agreement with measurements by Tosaya et al (1987).…”
Section: Discussionsupporting
confidence: 80%
“…Previously, Tosaya et al (1987) reported a significant decrease in measured attenuation with temperature for tar sand samples at ultrasonic frequencies. Thus, the theoretical result presented here is in qualitative agreement with their experimental result.…”
Section: Wave Propagation Modelingmentioning
confidence: 92%
See 1 more Smart Citation
“…Decreases in shearwave velocities were also observed, although to a lesser extent than the decrease in Pwave velocity. Lastly, Tosaya et al, (1987) proposed that, for high saturation levels, Pwave velocity can serve as a highly accurate reservoir thermometer for enhanced oil 5 recovery projects. However, Paulsson et al (1994) negated this, cautioning that actual temperatures cannot be derived from seismic velocities.…”
Section: Changes In P-wave Velocitymentioning
confidence: 99%
“…This raises the possibility of using seismic methods to detect temperature anomalies in reservoirs. Tosaya et al (1987) and Wang and Nur (1988) performed laboratory experiments to demonstrate the velocity and attenuation dependence on temperature for several heavy-oil/tar-sand samples. Wang et al (1990) measured acoustic velocities at ultrasonic frequency (800 kHz) in oil samples of different API as a function of temperature and pressure.…”
Section: Properties Of Heavy Oilmentioning
confidence: 99%